Chemical Speciation and Availability of Iron, Copper, Manganese and Nickel in Soils of Kashmir Himalayas - and M.A. Wani, Shazia Ramzan, M.A. Bhat (Journal of the Indian Society of Soil Science, 2016)
Chemical speciation was employed to estimate various chemical pools of iron (Fe), copper (Cu), manganese (Mn) and nickel (Ni) in soils of Kashmir Himalayas. Speciation studies were carried out by applying Tessier’s procedure, which allows subdividing the total metal content into six fractions (water soluble, exchangeable, bound to carbonates, bound to Fe-Mn oxides, bound to organic matter and residual fraction) representing portions bound to different components of the soil. Results indicated that the micronutrients were mainly retained by co-precipitation or incorporation into crystalline particles. Among micronutrients, Fe was mainly associated with the residual fraction (1363 mg kg-1) followed by oxide bound (390 mg kg-1), organic bound (373 mg kg-1), carbonate bound (42.6 mg kg-1) water soluble (8.24 mg kg-1) and least in exchangeable fraction (5.87 mg kg-1). Highest content of Cu was found to the residual fraction (28.9 mg kg-1) while lowest in carbonate fraction (1.57 mg kg-1). Both the Mn and Ni were mostly concentrated with residual (121.9 and 23.9 mg kg-1) and to the oxide bound (113.7 and 9.96 mg kg-1) fractions. Data showed that among four micronutrients, percentage of available fraction was highest for Mn (57.8%) and lowest for Cu (34.0%).